Fingerprint n°2 : the evolution of handmade elements in graphic design. - Chen, Joshua C., ....- (Cincinatti : How Books, 2011)
For many designers, creating things by hand is a reaction to too much computer-based design. Since the first Fingerprint was published, ideas that were once on the fringe have begun to thrive in the mainstream. From typography and illustration to book-making and film titles, elements of handcraft have soaked into everyday life. Fingerprint No. 2 reflects the evolution of those ideas. In this second volume, you'll still find plenty of projects created entirely without the aid of computer technology. But you'll also discover how designers are beining to incporate the two aesthetics - handmade and digital - in order to best communicate their message. A third, hybrid aesthetic is emerging, one that marries the technologies of the past and future into a vibrant, exciting present. Look inside to discover 133 projects and exclusive visual essays from leading designers, including Robynne Raye, Stefan Bucher and Christian Helms. These pieces of work prove that handmade elements are not only vital to excellent design, but often result in exceptional design.
Keywords: Affiches; Grafische vormgeving